Approximate Evolution for A Hybrid System—An Optomechanical Jaynes-Cummings Model - Medina-Dozal, Luis (Entropy (Basel), 2020)
In this work, we start from a phenomenological Hamiltonian built from two known systems: the Hamiltonian of a pumped optomechanical system and the Jaynes-Cummings Hamiltonian. Using algebraic techniques we construct an approximate time evolution operator [Formula: see text] for the forced optomechanical system (as a product of exponentials) and take the JC Hamiltonian as an interaction. We transform the later with [Formula: see text] to obtain a generalized interaction picture Hamiltonian which can be linearized and whose time evolution operator is written in a product form. The analytic results are compared with purely numerical calculations using the full Hamiltonian and the agreement between them is remarkable.